PENGARUH KEPEMIMPINAN, KOMUNIKASI, DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. KARDISA DENPASAR - Sugiartha, Pande Wayan Agus; Mujiati, Ni Wayan (E-Jurnal Manajemen; Vol 4 No 1 (2015), 2015)
The purpose of this study was to determine the influence of leadership, communication, and physical work environment on job satisfaction of employees at PT. Kardisa Denpasar. his study used a qualitative research using surveys and questionnaires to 61 employees of PT. Kardiasa Denpasar. The analysis technique used in this study is the multiple linear regression analysis. Obtained findings that leadership, communication, and physical work environment simultaneously significant effect on job satisfaction of employees at PT. Kardisa Denpasar. Other results found that leadership, communication, and physical work environment is partially positive and significant effect on job satisfaction of employees at PT. Kardisa Denpasar. Finally, the leadership variable is a variable that dominant influence on job satisfaction of employees of PT. Kardisa Denpasar.
Keywords: Kepemimpinan; Komunikasi; Lingkungan Kerja Fisik; Kepuasan Kerja